Large magnetoresistance in highly textured Mn44.7Ni43.5Sn11.8 melt spun ribbons. (13th April 2016) - Chen, Fenghua; Huang, Qingxue; Jiang, Zhengyi; Xuan, Haicheng; Zhang, Mingang; Xu, Xiaohong; Zhao, Jingwei
Abstract: Highly textured Heusler alloy Mn44.7 Ni43.5 Sn11.8 ribbons were prepared by melt spinning. The magnetoresistance (MR) properties were evaluated by the magnetic field perpendicular to the ribbon surface with the field up to 30 kOe. A large MR (about 25%) with a lower magnetic field (10 kOe) was obtained at 276 K. Due to the rapid solidification. The ribbons with a specific texture can get a large MR twice than polycrystalline alloys at the same magnetic field. The highly textured Mn–Ni–Sn melt spun ribbons may be broadly applied in magnetic memory and as temperature and magnetic sensors as well.